A Case Report of Bilateral Adrenal Sarcomatoid Carcinoma. (20th December 2016) - Turhan Iyidir, Ozlem; Cerit, Ethem Turgay; Özkan, Çiğdem; Altınova, Eroğlu; Çimen, Ali Rıza; Sözen, Sinan; Kerem, Mustafa; Aktürk, Müjde; Memiş, Leyla; Törüner, Baloş; Çakır, Nuri; Arslan, Metin
Abstract : Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy. Sarcomatoid adrenal carcinoma is even more aggressive type of ACC. Bilateral malignant adrenal tumors are extremely rare except for those that represent metastasis from an extra-adrenal organ. Here we report a 53-year-old woman who presented with abdominal pain and weight loss. Abdominal computed tomography revealed bilateral adrenal masses and a mass in her liver. Surgical specimens showed pleomorphic tumor cells with epithelial and spindle cell morphology and immunohistochemical staining was compatible with sarcomatoid carcinoma. Sarcomatoid adrenal carcinoma should be kept in mind during the management of bilateral adrenal masses.